UPAYA KONSERVASI EX SITU DIPTEROCARPACEAE DI KEBUN RAYA BOGOR - Rahayu, Eka Martha Della (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2009)
Malesia is the center of Dipterocarps diversity in the world, with most species found in Indonesia. Sadly, their existence is threatened by illegal logging, extensive exploitation, and habitat conversion. There are 143 Indonesian Dipterocarps categorized as threatened in the IUCN Red List. Bogor Botanic Garden (BBG) is one of the leading institutions focuses on ex situ conservation of plants. Dipterocarps collection in the BBG represents 41.5% of Dipterocarps of Sumatra, 17.0% of Dipterocarps of Kalimantan, 77.8% of Dipterocarps of Java, 66.7% of Dipterocarps of Bali and Nusa Tenggara, 57.1% of Dipterocarps of Sulawesi, 66.7% Dipterocarps of Moluccas, and 8.3% Dipterocarps of Papua. Totally, BBG has only conserved about 37.8% of threatened Indonesian Dipterocarps, still far from the target aimed by the Global Strategy for Plant Conservation (60% conserved). The BBG has initiated genetic resource conservation of Dipterocarps, through seed preservation. Since most Dipterocarps have recalcitrant seeds, conventional storage methods cannot be used. One of the alternative solutions is to cryopreserve the excised embryo or embryonic axes to overcome the limits of conventional storage methods. Collection of threatened and endemic species along with research on embryo culture and cryopreservation should be intensified in the future.